Problematika Manajemen Kesiswaan, Personalia dan Humas Beserta Pemecahan Masalahnya di Sekolah Dasar ( Studi Riset di SD Intis School Yogyakarta) - Permana Octofrezi (STAI Terpadu Yogyakarta, 2019)
Student management problems, personnel and public relations problems and their problem solving in elementary schools (Research Study at SD INTIS School Yogyakarta). The purpose of this research is to find out the concepts, roles and problems that occur in student management, personnel and community relations at school basic. In addition the authors provide solutions or problem solving for problems that occur. The method the researcher used was a descriptive qualitative research method with data sources through interviews with relevant school leaders. The results showed that the problems that occur in student management include: 1) Some students are inconsistent in following an extracurricular activity and tend to ask to move to another extracurricular, 2) the committee is less loyal to their duties, 3) the problem of uniforming student administration, 4) the number of agendas that are lacking supported by sufficient funds, 5) the existence of extracurriculars that are less effective and devoid of interest. In personnel management, the following problems were found: 1) there are those who have resigned annually, 2) the lack of training and development of human resources for educators and education staff. Whereas in public relations management problems are found: 1) Lack of staff or or limited human resources in the field of Public Relations, 2) In carrying out their duties and functions, Public Relations Employees lack expertise (competence), 3) Overlapping of work with one another, 4) Not having an adequate budget, 5) Sometimes the funds that have been budgeted turn out to be incompatible with reality on the ground. So that inevitably the public relations staff sometimes pack all the needs in accordance with what is budgeted.